Penerapan Dan Implementasi Sistem Informasi Perpustakaan Berbasis Web Di Perpustakaan Smk Modellink Kabupaten Sorong - Marcelinus Petrus Saptono; Luluk Suryani (Universitas Muhammadiyah Sorong, 2018)
Information technology is very responsible in the development of the library world. The role of technology is a computerized information system so as to improve performance to be more optimal. The increase in books and borrowing systems requires better, complete and factual management systems and services. This study aims to build a web-based information system at Modellink Vocational School in Sorong Regency that can be accessed online. The web-based library information system is built using Open Source Software (OSS) web devices using the Circular Library Management System (SLiMS) that supports AJAK (Asynchronous Javaskrip and XML) technology and can be run on Windows or Linux Operating Systems with PHP and MySQL RDBMS. Development of a web-based library information system using the Waterfall Method according to Pressman (2010).Â The results of this study proved to have been designed Web-based Library Management Information System Application at Modellink Vocational School in Sorong Regency which can be accessed online or offline that produces information about effective and efficient grouping management that makes features of loan transactions, returns, collection reservations, rules flexible lending, information and fines, making membership card membership, inventory management inventory (inventory), reports and statistics, issue management, management of multimedia documents and digital documents such as pdf. Detailed book descriptions are available in XLM (Extensible Markup Language) format for web service needs.